TANTANGAN JURNALIS EKONOMI DALAM PEMBERITAAN E-COMMERCE (Studi Analisa Nilai Berita Kompas.Com Periode Mei 2019) - ulfa Khairina (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2019)
This study examines the issueof the challenge of e-commerce reporting among economic journalists. The author reviews the challenge of selecting e-commerce news values by description analysis method with qualitative approach for the periode of May 2019 news articles according to e-commerce keyword search. The author found 28 articles discussing e-commerce on rubric mony with the sub-categories whats new, spend smart, earn smart, and work smart on http://money.kompas.id/. The results of this study showed only three news values selected by the Kompas news portal journalists, namely timeliness, consequence, and proximity. Journalist use an e-commerce perspective in describing articles that are published online. The main challenge of portal journalists is the length of articles written by incompatible with the effective read duration.